(untitled) (Acta Scientiarum. Biological Sciences, 2017)
Sciurus igniventris is a squirrel with broad distribution in South America. We examined one female adult specimen which was donated after death by trampling. The aim of this work was describe the morphological characteristics of mammary gland of one specimen. The body was fixed using 10% aqueous formaldehyde. Tissues were processed and slides prepared following standard histological protocols. Morphological analysis of the mammary glands revealed similarities to those described in the literature for domestic and wild mammals. As special features in kind, macroscopically identified a pair of thoracic glands, followed by three pairs of abdominal glands. Microscopically the abundant presence of connective tissue dividing the alveolar-tubular glands. Similar to that described for domestic and wild mammals.